Three-Layered Silk Fibroin Tubular Scaffold for the Repair and Regeneration of Small Caliber Blood Vessels: From Design to in vivo Pilot Tests - Alessandrino, Antonio; Chiarini, Anna; Biagiotti, Marco; Dal Prà, Ilaria; Bassani, Giulia A.; Vincoli, Valentina; Settembrini, Piergiorgio; Pierimarchi, Pasquale; Freddi, Giuliano; Armato, Ubaldo (Frontiers in Bioengineering and Biotechnology, 2019)
Silk fibroin (SF) is an eligible biomaterial for the development of small caliber vascular grafts for substitution, repair, and regeneration of blood vessels. This study presents the properties of a newly designed multi-layered SF tubular scaffold for vascular grafting (SilkGraf). The wall architecture consists of two electrospun layers (inner and outer) and an intermediate textile layer. The latter was designed to confer high mechanical performance and resistance on the device, while electrospun layers allow enhancing its biomimicry properties and host's tissues integration. In vitro cell interaction studies performed with adult Human Coronary Artery Endothelial Cells (HCAECs), Human Aortic Smooth Muscle Cells (HASMCs), and Human Aortic Adventitial Fibroblasts (HAAFs) demonstrated that the electrospun layers favor cell adhesion, survival and growth. Once cultured in vitro on the SF scaffold the three cell types showed an active metabolism (consumption of glucose and glutamine, release of lactate), and proliferation for up to 20 days. HAAF cells grown on SF showed a significantly lower synthesis of type I procollagen than on polystyrene, meaning a lower fibrotic effect of the SF substrate. The cytokine and chemokine expression patterns were investigated to evaluate the cells’ proliferative and pro-inflammatory attitude. Interestingly, no significant amounts of truly pro-inflammatory cytokines were secreted by any of the three cell types which exhibited a clearly proliferative profile. Good hemocompatibility was observed by complement activation, hemolysis, and hematology assays. Finally, the results of an in vivo preliminary pilot trial on minipig and sheep to assess the functional behavior of implanted SF-based vascular graft identified the sheep as the more apt animal model for next medium-to-long term preclinical trials.